Cervical Myelopathy due to Congenital Atlanto-axial Dislocation - Rana, PVS; Shetti, Mohit P.; Thapa, Lekhjung (Nepal Journal of Neuroscience, 2005)
Five cases of atlanto-axial dislocation (AAD) are reported with emphasis on their clinical presentation and literature is reviewed. The first patient had gross AAD and presented as progressive myelopathy. The second patient had AAD with occipitalization of atlas, Chiari malformation and syringomyelia where headache was the only presenting symptom. The third patient with AAD, had occipitalization of atlas and fusion of cervical second and third (C2- C3) vertebrae. She presented with peculiar sensation over forehead. Detection of pathologically brisk tendon reflexes in the lower limbs and extensor plantar response led to further investigation and diagnosis of the condition. The fourth patient had AAD and advanced spondylotic changes. His symptoms manifested after injury and then progressed gradually leading to quadriplegia. The fifth case presented with nuchal and occipital neuralgia, paresthesia in hands and brisk reflexes. X-ray cervical spine showed unfused, separate but fully developed odontoid process and AAD. All these patients represented congenital AAD. Nepal Journal of Neuroscience, Volume 2, Number 1, 2005, Page 71-76